Taxonomic diversity and abundance of enchytraeids (Annelida, Clitellata, Enchytraeida) in the Northern Palaearctic. 1. Asian part - Degtyarev, Maxim; Saifutdinov, Ruslan; Korobushkin, Daniil; Bastrakov, Alexander; Danilova, Margarita; Davydov, Ivan; Gorbunova, Anastasia; Guseva, Polina; Karlik, Evgeniy; Koshchanova, Roza; Kuznetsova, Ksenia; Lebedev, Iurii; et al. (Pensoft Publishers, 2024)
Enchytraeids, or potworms, are tiny oligochaetes that are distributed worldwide in many terrestrial, freshwater and marine ecosystems. Despite their key role in the functioning of ecosystems, the diversity and abundance of Enchytraeidae are rarely studied due to the laborious process of species identification. The present study addresses this gap and sheds some light on the distribution and abundance of enchytraeids in the lands of the Northern Palearctic. The provided dataset constitutes the latest and comprehensive field sampling of enchytraeid assemblages across the Asiatic part of the Northern Palearctic, encompassing an original set of soil samples systematically collected throughout the region from 2019 to 2022. The dataset includes occurrences from 131 georeferenced sites, encompassing 39 species and 7,074 records. This represents the first dataset providing species-specific information about the distribution and abundance of terrestrial enchytraeids across an extensive geographic area covering the Asian sector of the Northern Palaearctic. The compiled dataset is the key for exploring and understanding local and regional enchytraeid diversity. It may also serve as a valuable resource for monitoring and conserving the entire soil biodiversity.